Free Learning Movement Teacher Program; Teachers' Efforts to Reconstruct the Quality of Education in Schools - Ahmad Zubaidi; Rizqi Amelia Putri; Muhamad Fajri (At-Tarbiyat, 2022)
This study aims to determine, find and analyze the comparison of Saudi Arabia’s Islamic education in terms of the structure and curriculum of Saudi Arabia’s Islamic educational institutions. This study uses a literature research method which is carried out through the study of several books, literature articles, and other documents that are reviewed in accordance with the Saudi Arabian Education Policy Study. The results of this study are as follows: First, the structure of Islamic educational institutions in Pend, a kindergarten in Saudi Arabia. Basically delayed. Secondary, pending. Secondary, pending. Big. Second, the curriculum of the Saudi Arabian Islamic Education Institute is also an integration of religious and general knowledge, and Saudi Arabia’s religious and general sciences are included in the education model there.